CaH Rydberg series, oscillator strengths and photoionization cross sections from Molecular Quantum Defect and Dyson Orbital theories. (January 2017) - Velasco, A.M.; Lavín, C.; Díaz-Tinoco, Manuel; Ortiz, J.V.
Abstract: In this work, electron-propagator methods are applied to the calculation of the ionization potential and vertical excitation energies for several Rydberg series of the CaH molecule. The present calculations cover more highly excited states than those previously reported. In particular, excitation energies for n s ( n >5), n p ( n >5), n d ( n >4) and n f Rydberg states are given. Oscillator strengths for electronic transitions involving Rydberg states of CaH, as well as photoionization cross sections for Rydberg channels, also have been determined by using the Molecular Quantum Defect Orbital approach. Good agreement has been found with the scarce comparative data that are available for oscillator strengths. To our knowledge, predictions of photoionization cross sections from the outermost orbital of CaH are made here for the first time. A Cooper minimum and mixed atomic orbital character in some of the Dyson orbitals are among the novel features of these present calculations. Highlights: Two theoretical methods are combined to make predictions on a molecule of interest in astrochemistry and related fields. A Cooper minimum in photoionization cross sections is predicted. Hybridization is important in several diffuse Dyson orbitals that correspond to addition of electrons to CaH + to form highly excited states of CaH.